Dephosphorylation of Caveolin-1 Controls C-X-C Motif Chemokine Ligand 10 Secretion in Mesenchymal Stem Cells to Regulate the Process of Wound Healing - Wang, Panpan; Zhao, Yingji; Wang, Juan; Wu, Zhiying; Sui, Bingdong; Mao, Xueli; Shi, Songtao; Kou, Xiaoxing (Frontiers in Cell and Developmental Biology, 2021)
Mesenchymal stem cells (MSCs) secrete cytokines in a paracrine or autocrine manner to regulate immune response and tissue regeneration. Our previous research revealed that MSCs use the complex of Fas/Fas-associated phosphatase-1 (Fap-1)/caveolin-1 (Cav-1) mediated exocytotic process to regulate cytokine and small extracellular vesicles secretion, which contributes to accelerated wound healing. However, the detailed underlying mechanism of cytokine secretion controlled by Cav-1 remains to be explored. We show that gingival MSCs (GMSCs) could secrete more C-X-C motif chemokine ligand 10 (CXCL10) but showed lower phospho-Cav-1 (p-Cav-1) expression than skin MSCs (SMSCs). Moreover, dephosphorylation of Cav-1 by a Src kinase inhibitor PP2 significantly enhances CXCL10 secretion, while activate phosphorylation of Cav-1 by H2O2 restraints CXCL10 secretion in GMSCs. We also found that Fas and Fap-1 contribute to the dephosphorylation of Cav-1 to elevate CXCL10 secretion. Tumor necrosis factor-α serves as an activator to up-regulate Fas, Fap-1, and down-regulate p-Cav-1 expression to promote CXCL10 release. Furthermore, local applying p-Cav-1 inhibitor PP2 could accelerate wound healing, reduce the expression of α-smooth muscle actin and increase cleaved-caspase 3 expression. These results indicated that dephosphorylation of Cav-1 could inhibit fibrosis during wound healing. The present study establishes a previously unknown role of p-Cav-1 in controlling cytokine release of MSC and may present a potential therapeutic approach for promoting scarless wound healing.